2017
DOI: 10.1111/jgh.13587
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of daclatasvir plus asunaprevir for hepatitis C virus genotype 1b: Systematic review and meta‐analysis

Abstract: Daclatasvir plus asunaprevir provides a highly effective and well-tolerated treatment option for patients with HCV genotype 1b. However, patients with nonstructural protein 5A RAVs at baseline should be assessed to optimize more potent direct antiviral agent therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
3
16
2
Order By: Relevance
“…Two meta‐analysis have been reported regarding the correlation between HCV‐RNA levels and treatment response of this regimen. Wang et al showed that patients with a viral load of <8 × 10 5 had a tendency to have higher SVR rate compared with patients with a viral load of ≧8 × 10 5 . In contrast, Kao et al showed no difference between patients with a viral load of <3 × 10 6 and ≧3 × 10 6 ; the cutoff level in the latter study was almost the same as those of the present study …”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Two meta‐analysis have been reported regarding the correlation between HCV‐RNA levels and treatment response of this regimen. Wang et al showed that patients with a viral load of <8 × 10 5 had a tendency to have higher SVR rate compared with patients with a viral load of ≧8 × 10 5 . In contrast, Kao et al showed no difference between patients with a viral load of <3 × 10 6 and ≧3 × 10 6 ; the cutoff level in the latter study was almost the same as those of the present study …”
Section: Discussionsupporting
confidence: 54%
“…Wang et al 27 showed that patients with a viral load of <8 × 10 5 had a tendency to have higher SVR rate compared with patients with a viral load of ≧8 × 10 5 . 27 In contrast, Kao et al 28 showed no difference between patients with a viral load of <3 × 10 6 and ≧3 × 10 6 ; the cutoff level in the latter study was almost the same as those of the present study. 28 RVR has also been identified as a predictive on-treatment factor of SVR12.…”
Section: Discussionmentioning
confidence: 99%
“…The SVR rate in PP analysis (95.8%), which excluded those who discontinued the combination therapy due to nonmedical reasons, was higher in previously published studies . Notably, the treatment withdrawal rate in treatment‐experienced patients was very low (2/162, 1.2%), so that the SVR rate in those patients was not inferior to treatment‐naive patients.…”
Section: Discussionmentioning
confidence: 77%
“…This may be attributable to the Korean practice under Government insurance system requiring mandatory pretreatment testing for RAS. Because the SVR rate in RAS‐negative patients was consistently higher than those with RAS (usually <70%) in previous studies, recent post‐2016 real‐world studies from Korea did not include RAS‐positive patients, resulting in a more favorable treatment response rate compared with former studies …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation